Impact of the organisational culture on primary care staff members' intention to engage in research and development. Issue 2 (13th April 2015) - Morténius, Helena; Baigi, Amir; Palm, Lars; Fridlund, Bengt; Björkelund, Cecilia; Hedberg, Berith
Abstract : Purpose: – The purpose of this paper is to understand how organisational culture influences the intentions of primary care staff members (PCSM) to engage in research and development (R&D). Design/methodology/approach: – The participants ( n =30) were PCSM employed in a care centre in south-western Sweden. The study had an observational design with an ethnographic approach. The data were collected by means of observations, interviews and analysis of documents. Findings: – The results revealed the perceptions of PCSM in two domains, research and clinical practice, both of which existed at three different cultural levels: visible (structures and policy), semi-visible (norms and values) and invisible (taken-for-granted attitudes). Research limitations/implications: – It is difficult to conduct a purely objective ethnographic study because the investigation is controlled by its context. However, it is necessary to highlight and discuss the invisible level to improve understanding of negative attitudes and preconceptions related to the implementation of R&D in the clinical setting. Practical implications: – By highlighting the invisible level of culture, the management of an organisation has the opportunity to initiate discussion of issues related to concealed norms and values as well as attitudes towards new thinking and change in the primary health context. Originality/value: – This paper is one of the very few studies to investigate the influence of organisational culture on the intentions of PCSM to engage in R&D.